Validitas dan Reliabilitas Instrumen Deteksi Ide Bunuh Diri pada Remaja - Anisa Siti Nurjanah; Yulia Ayriza; Sindi Ayudia Pama; Syarifudin Syarifudin (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
The identification of suicidal ideation is a crucial first step in comprehensive suicide prevention efforts because it enables timely intervention and appropriate support for individuals at risk. To ensure accuracy, the assessment process requires a measurement instrument that has been empirically tested and proven suitable for the intended population. This study aimed to validate a suicidal ideation detection instrument to confirm its readiness for practical application. The instrument was developed using a research-and-development approach guided by Saifuddin Azwar’s scale development design. The development procedures included defining measurement objectives, determining the measurement domain, operationalizing the construct, preparing a scale blueprint, formulating items, conducting qualitative reviews, carrying out pilot testing, performing item analysis, compiling the initial draft, selecting qualified items, and continuing with reliability and validity testing before producing the final instrument format. Content validity was assessed by three expert validators, followed by field testing involving 200 students. Quantitative data were analyzed using JASP version 0.16 software. The findings showed that the suicidal ideation detection instrument met the required validity criteria, demonstrated by an Aiken’s V coefficient categorized as high (0.866). Additionally, all items exhibited strong discrimination, and the overall reliability score reached 0.926, confirming that the instrument is suitable and effective for early detection among students._____________________________________________________________Deteksi ide bunuh diri sangat penting dilakukan sebagai tahap awal upaya pencegahan bunuh diri. Deteksi ide bunuh diri harus dilakukan menggunakan instrumen asesmen yang telah teruji valid dan layak digunakan. Penelitian ini berusaha melakukan validasi pada instrumen asesmen deteksi ide bunuh diri agar siap digunakan. Pengembangan instrumen menggunakan metode R&D dengan desain penyusunan skala Saifuddin Azwar. Adapun langkah penyusnan yaitu identifikasi tujuan ukur, pembatasan domain ukur, operasionalisasi konsep, penelitian item berdasarkan indikator yang disajikan dalam kisi-kisi skala, reviu kualitatif, uji coba, analisis item, kompilasi I seleksi item, pengujian reliabilitas, validasi, dan kompilasi II format final. Pengujian validitas dilakukan oleh tiga orang validator ahli, dan diujicobakan pada 200 siswa untuk uji validitas. Pengujian kuantitatif dilakukan menggunakan bantuan aplikasi JASP versi 0.16. Hasil menunjukkan bahwa instrumen asesmen deteksi ide bunuh diri valid digunakan karena memenuhi syarat validitas nilai Aiken’s V pada kategori tinggi dengan nilai 0,866. Instrumen memperoleh nilai tinggi pada tiap butir item pada uji daya diskriminasi, dan memiliki reliabilitas tinggi dengan skor 0,926.